(حكم تثنية المصدر المبين للنوع وجمعه (دراسة نقدية - Zainal Abidin Hajib; Maskanatul Fiqiyah; Hishomudin Ahmad (Universiti Islam Darussalam- UNIDA Gontor, 2024)
The present knowledge of Arabic grammar was not structurally studied in Jahiliyyah period and early Islamic periods by companions of Prophet Muhammad PBUH. The Arab spoke their language fluently without any linguistic barriers in their tongue. The Arabic grammar was introduced after Islam was spread among non-Arab in neighboring countries. Muslim scholars began to protect Arabic language principles from misused by non-Arab speakers through compiling Arabic grammar from Arabian tribes and Bedouins in Middle of Arabian Peninsula, the original homeland of the Arab people. Among the prominent Arabic grammarian scholars in 8th century of Hijrah was al-Syatibi. While writing his great Arabic grammar book, al-Maqasid as-Syafiyyah li Sarhi Alfiyyah Ibn Malik, he criticized another scholars arguments and formed his own opinions. In addition al-Syatibi also did not follow any school of thoughts without any arguments or proofs. This paper aims to analyzed the al-Syatibi’s opinion on the possibility of using dual or plural form on verbal noun or gerund. Analytical method was employed by comparing grammarians’ opinions from various type of books. The convincing arguments were used in the judgement by using strong opinions. The result showed al-Syatibi agreed on the possibility of using dual or plural form on verbal noun. It was supported by az-Zajjaji and Ibn Malik’s opinions in their books.